Model Pengembangan Asesmen Hots dalam Keterampilan Menulis Teks Prosedur Fase D - Siti Faridah; Kuntoro Kuntoro (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The evaluation of Indonesian language instruction at the junior secondary level remains predominantly oriented toward lower-order thinking skills, thereby constraining the advancement of students’Higher Order Thinking Skills (HOTS). This situation necessitates the development of comprehensive assessment tools that are coherently aligned with the Merdeka Curriculum. The present study introduces a model for constructing HOTS-oriented assessment instruments targeting procedural text writing in Phase D. The development process was systematically organized through several stages: translating learning outcomes into measurable indicators, preparing assessment blueprints, creating item cards, formulating scoring rubrics for attitudes, knowledge, and skills, and finally analyzing and interpreting the assessment data. These instruments were specifically designed to capture students’ analytical, evaluative, and creative abilities in producing procedural texts that are logical, coherent, and effective. Findings demonstrate that the instruments provide an objective and holistic representation of students’ competency attainment. In summary, the proposed HOTS-based assessment model for procedural text writing is practical, methodical, and contextually relevant, serving as a valuable framework for evaluating Indonesian language learning in accordance with the Merdeka Curriculum principles.